Gender roles and their implications in intercultural communication process (2016)
This literature review, searches for better understanding the implications of gender roles differences when intercultural communication takes place in societies. This research suggests that the differences in male and female communication styles affect and have an influence when communicating with people from another cultures. The cultural barriers in societies are massive referring to differences and stereotypes are the main reason for this barriers to exist. This document seeks to define gender stereotypes and their impact in interculturality. In addition, this paper explains and makes a contrast in women and men communication in relation with human behavior. As main conclusion of this document it can be argued that gender roles and stereotypes affect intercultural communication processes and create a social impact that hinders the expression of ideas and thoughts between men and women.